ANALISIS PENGARUH LOCUS OF CONTROL DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN SELF EFFICACY SEBAGAI MEDIASI (Studi pada Dinas Pertanian dan Kehutanan Kabupaten Rembang) - Riva'i, Alimuddin Rizal; Rofiana, Lulu’ (Jurnal Ilmiah Telaah Manajemen, 2014)
The purpose of this study was to determine the effect of locus of control and work environment on employee performance with self efficacy mediation. In this study the dependentvariable is the employee performance, while the independent variable is the locus of control andwork environment and self-efficacy as an intervening variable (mediation). This research was conducted at the Department of Agriculture and Forestry Rembangregency. The method of data collection was done by using a questionnaire that census sample totaled 103 people. The results showed that the locus of control is significant positive effect on self-efficacybut not significant effect on the employee performance, work environment significant positive effect on self-efficacy and employee performance while self-efficacy significant positive effect onemployee performance and an intervening variable (mediation) between locus of control andemployee performance. Keywords : locus of control, work environment, self efficacy and employee performance